BIMBINGAN TEKNIS PENGGUNAAN VACUM FRYING & PENINGKATAN JARINGAN PEMASARAN PADA UMKM PRODUSEN KRIPIK - Prayitno; Sri Rulianah; Achmad Zaini (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
UD. Favoriet is one of the SMEs in Pandaan - Pasuruan which was established in 2008, where this UMKM produces several snack products (Kripik), including: banana chips, meatball chips, crispy cashews & oven cashews, crispy peanuts & oven nuts. These products have been marketed to several areas, including: Pasuruan, Sidoarjo and Malang. However, UD Favoriet in production still operates manually (non-mechanically), does not apply the principles of healthy and good production, as well as the conventional marketing system. At the time of the Covid-19 pandemic, as now, the condition of SMEs experienced a decline in production and sales of up to 60% - 70%. The purpose of PPM Partnership is to increase production capacity, improve product quality, improve a good understanding of production, and increase sales turnover. PPM activities, among others: 1). grant of vacuum frying equipment and sealer, 2). GMP and HACCP training, 3). training in making online marketing media (online marketing). The results of PPM activities include changes in the production system from manual to mechanical, product quality improvement, increased understanding of healthy and safe production methods, and changes in the marketing system from customer to customer to online marketing